Electrocardiographic Changes in Pregnant Patients With Congenital Heart Disease - Maria A. Pabon; Amrit Misra; Kimberlee Gauvreau; Madeline E. Duncan; Ava Conklin; Katherine E. Economy; Fred M. Wu; Thomas Tadros; Anne Marie Valente; For the STORCC Investigators (Annals of Noninvasive Electrocardiology, 2025)
ABSTRACT Background Electrocardiograms (EKGs) are routinely performed in pregnant patients with pre‐existing cardiovascular disease. However, in pregnant patients with congenital heart disease (CHD), EKG changes during gestation have not been explored. Methods We performed a retrospective study of pregnant patients with CHD enrolled in the STORCC initiative. Patients were included if they had at least two EKGs across the perinatal period and were grouped by specific conditions: atrial septal defect (ASD), tetralogy of Fallot, congenital pulmonary stenosis, coarctation of the aorta (CoA), bicuspid aortic valve (BAV), systemic right ventricle (SRV), and Fontan circulation. EKG parameters were measured in all available EKGs by two investigators, blinded to diagnosis and time of gestation. Results One hundred and seventy pregnant patients were included. There was a statistically significant increase in HR from pre‐pregnancy to third trimester in all groups except for those with Fontan and SRV. Patients with ASD and BAV had a statistically significant increase in their QTc (ASD:13 ms, p = 0.017; BAV:7 ms, p = 0.018) during pregnancy. QRS duration was shorter (4 ms) in the third trimester for patients with ASD (p = 0.033) and CoA (p = 0.014). Despite these individual findings, EKG parameters remained within normal limits and regressed to baseline in the postpartum period. Conclusions Patients with CHD have statistically significant EKG changes throughout pregnancy, but the values remain within normal limits. Like patients without heart disease, those with CHD increase their HR during pregnancy, except individuals with SRV and Fontan, who appear to lack capacity for physiologic HR augmentation.